Hjemfaldne himmelstormere: Rum, atmosfære og vejr i Kongens Fald - Ballebye Sørensen, Caroline (Passage - Tidsskrift for litteratur og kritik, 2022)
In recent years, theories of space, atmosphere and weather have gained a foothold in literary analysis. In this article, I interpret Johannes V. Jensen’s canonical work of fiction The Fall of the King (1900-1901) on the basis of the spatial surroundings that the novel creates and that revolve around the protagonist Mikkel Thøgersen. I thereby claim that not only space, but also atmosphere and weather evoke different epistemologies that conflict throughout the novel. Last but not least I position the phenomenology of weather in The Fall of the King to Jensen’s oeuvre to emphasize that Jensen was an exemplary weather maker in Danish literary history.